Physical, chemical, microbiological properties and shelf life kinetic of spray-dried cantaloupe juice powder during storage - Tan, Suet Lin; Sulaiman, Rabiha; Rukayadi, Yaya; Ramli, Nurul Shazini (Elsevier, 2020)
Cantaloupe contains many bioactive compounds such as phenolic, flavonoid, and carotenoid. Cantaloupe powder was produced by spray drying with gum arabic as the carrier agent, and stored for 180 days at ambient (25 ± 2 °C, 50–70% RH) and accelerated conditions (38 ± 2 °C, 90% RH). The effects of storage conditions on the physicochemical and microbiological properties of spray-dried cantaloupe powder were evaluated. In both storage conditions, the moisture content, water activity, and total color difference of the spray-dried cantaloupe powder increased with storage duration, while the hygroscopicity and total carotenoid content decreased with storage duration. The degradation of carotenoid content in the spray-dried cantaloupe powder followed first-order kinetics. The half-lives of cantaloupe powder stored in ambient and accelerated conditions were estimated as 28.41 and 25.11 days, respectively. Microbial results of spray-dried cantaloupe powder for 180 days of storage in both conditions were in acceptable limit.